2024
DOI: 10.1590/s1678-9946202466003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial resistance profile of pathogens isolated from patients with urine tract infections admitted to a university hospital in a medium-sized Brazilian city

Mariana Negri,
Bárbara Martins Lima,
Renata dos Santos Batista Reis Woloszynek
et al.

Abstract: This study aimed to determine the antibiotic profile of microorganisms isolated from urine samples of patients with community urine tract infections (UTI) admitted to the University Hospital of the Federal University of Sao Carlos to support an appropriate local empirical treatment. A retrospective cross-sectional study was conducted from October 2018 to October 2020. Data from 1,528 positive urine cultures for bacterial pathogens and antibiograms were tabulated. Bacterial species prevalence and their resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This result was in line with a study conducted in Brazil that reported that the prevalence of E. coli in women was 1.5 times greater than that in men. 30 In addition, a study conducted in Bangladesh revealed that the prevalence of E. coli was 63.6% in women and 36.4% in men. 31 Moreover, this result was in agreement with a study conducted in Peshawar, Pakistan, which reported that the prevalence of E. coli in female patients was 72.7%.…”
mentioning
confidence: 99%
“…This result was in line with a study conducted in Brazil that reported that the prevalence of E. coli in women was 1.5 times greater than that in men. 30 In addition, a study conducted in Bangladesh revealed that the prevalence of E. coli was 63.6% in women and 36.4% in men. 31 Moreover, this result was in agreement with a study conducted in Peshawar, Pakistan, which reported that the prevalence of E. coli in female patients was 72.7%.…”
mentioning
confidence: 99%